Lessons Learned From the Creating Active Communities and Healthy Environments Toolkit Pilot: A Qualitative Study - Marissa M Shams-White; Alison Cuccia; Fernando Ona; Steven Bullock; Kenneth Chui; Nicola McKeown; Aviva Must (SAGE Publishing, 2019)
The US Army Public Health Center developed the Creating Active Communities and Healthy Environments (CACHE) Toolkit to help military installations evaluate the quality of their built environments relative to healthy eating, physical activity, and tobacco-free living. This study sought to improve its implementation process and assess subsequent Action Plan Guides' utility at 5 military installations. Baseline data included a knowledge, attitudes, and beliefs survey (N = 34); post-Toolkit implementation data included focus groups (N = 2) and interviews (N = 10). Although >80% of participants agreed the built environment affects healthy living, only 44%, 53%, and 35% agreed their installations' built environments promoted healthy eating, physical activity, and tobacco-free living, respectively. Emerging themes comprised "Opportunities to Improve Toolkit and Action Plan Guide Functionality," the "Sociopolitical Landscape Affects Toolkit Implementation," and the "Sociopolitical and Physical Landscapes Affect the Toolkit's Value and Utility." This study provides concrete lessons for the CACHE Toolkit and other public health-based military initiatives.